2017
DOI: 10.3389/fpsyg.2017.00853
|View full text |Cite
|
Sign up to set email alerts
|

Self-Concept in Childhood: The Role of Body Image and Sport Practice

Abstract: The purpose of this study was to explore the differences in satisfaction with body image depending on whether the subject practices organized sport or not, as well as the gender of the children. In addition, the study aims to examine the role of body image and the practice of organized sport on the process of building the academic, social, emotional, family and physical dimensions of self-concept in childhood. To do so, a sample of 944 pupils was used. These children were attending primary school in different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
33
0
10

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(60 citation statements)
references
References 39 publications
4
33
0
10
Order By: Relevance
“…These data are alarming, taking into account the studies that have shown that body dissatisfaction is linked to negative and maladaptive consequences of children's behavior, such as the development of eating behavior disorders [16,17], and low levels of physical activity [29]. Therefore, before such dissatisfaction can lead to behaviors that are consolidated and harmful for children's health, it is necessary to intervene in the schools, where the subject of Physical Education could be a crucial aspect [30,31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These data are alarming, taking into account the studies that have shown that body dissatisfaction is linked to negative and maladaptive consequences of children's behavior, such as the development of eating behavior disorders [16,17], and low levels of physical activity [29]. Therefore, before such dissatisfaction can lead to behaviors that are consolidated and harmful for children's health, it is necessary to intervene in the schools, where the subject of Physical Education could be a crucial aspect [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, the way people perceive, feel, and behave in relation to their own body may be associated with high body satisfaction or body dissatisfaction. If not properly controlled or directed, this can cause serious consequences, such as the development of eating behavior disorders [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…For example, recent studies on physical and exercise domains carried out with community samples of Spanish adolescents, evidenced that gender stereotypes, body image, and sport practice showed different relations with academic, physical, emotional and family self-concept (Mendo-Lázaro et al, 2017); moreover, physical activity during adolescence improves physical self-concept, integration into peer groups and academic results (Martínez and Hernández, 2017); sampling young adult Chilean judo-practitioners, it was revealed that motivational climate was related to physical self-concept and satisfaction with the task (Ortega et al, 2017). Clinical studies have shown, in a children and adolescents community sample, that food neophobia presented different associations with social, physical, and academic self-concept (Maiz and Balluerka, 2018); furthermore, an emotional intelligence program for women with breast cancer showed general increase on the five AF5 self-concept factor scores and a decrease in anxiety (Cejudo et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…More specifically, it has been shown that self-concept is a factor associated with physical and sporting activity [22,23], so that those who regularly practice sport have a higher self-concept [24], particularly the physical self-concept [25,26] but also with all the self-concept dimensions [27]. But we would like to analyse the relation between the number of hours of organized sports practice and self-concept as a function of gender.…”
Section: Introductionmentioning
confidence: 99%